(untitled) (Contemporary Issues on Indonesian Human Rights Law and Policy, 2025)
This paper explores the tension between religious blasphemy laws and freedom of belief in Indonesia, a country known for its religious diversity but also for the strict enforcement of laws that criminalize blasphemy. The study provides an analysis of Indonesia’s blasphemy laws, particularly the 1965 Anti-Blasphemy Law, and its implications for freedom of expression and religious freedoms. By analyzing court cases, legal texts, and interviews with religious leaders, legal scholars, and human rights activists, the paper examines how these laws are applied in contemporary Indonesia. The research highlights cases where individuals have been prosecuted for expressing beliefs or engaging in religious practices that contradict mainstream interpretations of Islam, Christianity, and other religions. The paper argues that while the laws are often framed as protecting public order and interfaith harmony, they disproportionately restrict freedom of belief and expression, especially for religious minorities and non-conformists. The study concludes by discussing the broader human rights implications of such laws and proposing legal reforms that would better protect the right to freedom of religion and belief in Indonesia.